A apropriação/incorporação da língua inglesa pelo/no discurso empresarial : uma análise discursiva - Labandeira, Déborah Maria (2008)
The present work has the objective to investigate the meaning effects produced by the ppropriation/incorporation that the business speech makes of words or expressions in the English language. In order to do that, we have selected a corpus constituted by texts published in the Exame Magazine and in Pequenas Empresas & Grandes Negocios Magazine, in a period from March to December of 2006. We tried to analyze, in the speeches of these magazines, if the words or expressions in English are considered foreign words or linguistic lending and if it happens an appropriation or incorporation of these elements by the business speech. Besides that we identified the presence of a dominant ideology in the business speech and we verified how it happens the determination of the subjects that participate of the constitution of this speech. The work was divided in three chapters. In the first chapter we built a trajectory, which regards Saussure, Benveniste, Bakhtin and Pêcheux about language. In the second chapter, we ran over about concepts mobilized by the theory of the french Speech Analysis, such as speech and production conditions, interspeech and intraspeech, subject and ideology, speech formation, designation and silence. Finally, in the third chapter, we introduce the analyses of the speech sequences. The business speech, concerning the designations in English, sometimes appropriates them, sometimes incorporate them, attending to the interests of the dominant capitalism